HUKUM PROGRESIF SEBAGAI SOLUSI HUKUM YANG MENSEJAHTERAKAN RAKYAT - Mukhidin . (UNISSULA, 2014)
To get out of the slump legal situation in Indonesia, then there must be self-liberation from the conventional way of working madhhab inherited by positive law with all its doctrines and procedures that completely formal procedural fairness that it gave birth to the formal not substantial justice. Enlightenment and liberation from the shackles of the formal procedural course can only be reached through a progressive legal paradigm very concerned about the truth, humanity and justice. Is not that a law exists amongst the people is not only restricted to achieve certainty, but that is far greater than it is to achieve true justice for the welfare of the people. It can only be realized and obtained through a progressive law enforcement.